1991
DOI: 10.1104/pp.96.2.390
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of β-1,3-Glucanase Messenger RNAs in Response to Pathogen Infection

Abstract: The acidic, extracellular, glucan endo-1,3-t8-glucosidases (EC 3.2.1.39; j0-1,3-glucanases), pathogenesis-related proteins-2, -N, and -O (i.e. PR-2, PR-N, and PR-0) were purified from Nicotiana tabacum (tobacco) and their partial amino acid sequences determined. Based on these data, complementary DNA (cDNA) clones encoding the proteins were isolated. Additional cDNAs were isolated that encoded proteins approximately 90% identical with PR-2, PR-N, and PR-0. Although the proteins encoded by these cDNAs have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 27 publications
3
102
2
Order By: Relevance
“…β-1,3-glucanases genes comprise a large gene family that has been subdivided into three major classes based on their primary structures (Neale et al 1990;Payne et al 1990;Ward et al 1991). It has been reported that plants express β-1,3-glucanase genes (I, II, and III) in response to fungal and viral infections (Dobnik et al 2013;Linthorst et al 1990;Sela-Buurlage et al 1993;Ward et al 1991;Zavaliev et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-1,3-glucanases genes comprise a large gene family that has been subdivided into three major classes based on their primary structures (Neale et al 1990;Payne et al 1990;Ward et al 1991). It has been reported that plants express β-1,3-glucanase genes (I, II, and III) in response to fungal and viral infections (Dobnik et al 2013;Linthorst et al 1990;Sela-Buurlage et al 1993;Ward et al 1991;Zavaliev et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plants express β-1,3-glucanase genes (I, II, and III) in response to fungal and viral infections (Dobnik et al 2013;Linthorst et al 1990;Sela-Buurlage et al 1993;Ward et al 1991;Zavaliev et al 2011). In V. vinifera, 16 β-1,3-glucanases are present, but only five are basic proteins, and one of them contains both the N-and C-terminal signal peptide sequences (Jaillon et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these substances are used by the plants to create adverse conditions or may attack the pathogen directly (Beart et al, 1985;Friend, 1991). Similarly to the secretion of S. glaziovii, only one soluble β-1,3-glucanase exists in celery (Stephen and Rebecca, 1993), unlike in other species of plants, where different isoforms of Chitinase and β-1,3-glucanase usually exist (Pegg and Yong, 1981;Kauffmann et al, 1987;Mauch et al, 1988;Ward et al, 1991). The detection of a β-1,3-glucanase in the S. glaziovii secretion, confirmed by enzymatic assay after a SDS-PAGE suggested that the exuded protein secretion possesses a defense role.…”
Section: Discussionmentioning
confidence: 99%
“…therein). Three major classes (1-111) of /3-1,3-endoglucanases are also found in this plant species (Ward et al, 1991). The class I hydrolases are localized in the plant vacuoles and are potent inhibitors of growth in vitro of many fungi.…”
Section: Chitinases and /3-13-glucanasesmentioning
confidence: 91%